An analysis of citation counts of ETRI-invented US patents - Lee, Yong-Gil; Lee, Jeong-Dong; Song, Yong-Il (ELECTRONICS TELECOMMUNICATIONS RESEARCH INST, 2006)
From its foundation until 2004, ETRI has registered over 1,000 US patents This letter analyzes the characteristics of these patents and addresses the explanatory factors affecting their citation counts. For explanatory variables, research team related variables, invention specific variables, and geographical domain related variables are suggested. Zero-altered count data models are used to test the impact of independent variables. A key finding is that technological cumulativeness, the scale of invention, outputs in the electronic field, and the degree of dependence on the US technology domain positively affect the citation counts of ETRI-invented US patents. The magnitude of international presence appears to negatively affect the citation counts of ETRI-invented US patents.
Keywords: REGRESSION